Epistemic uncertainty in the analytically derived fragility functions : multiple stripe analysis versus cloud analysis - Önder, Zeynep Eda. (Thesis (M.S.) - Bogazici University. Kandilli Observatory and Earthquake Research Institute, 2022., 2022)
This study aims to examine the effects of epistemic uncertainty arising from dif ferent analysis approaches on the derived fragility functions. To this end, fragility functions are developed by using two different methods namely multiple stripe analysis (MSA) and cloud analysis, and compared for low-rise and mid-rise (3 and 6-story), re inforced concrete (RC), moment-resisting frame (MRF) buildings designed as per the Turkish Seismic Codes (TSC) published in 1975 and 2018. Each building’s prelimi nary design complies with the minimum requirements specified in the relevant seismic codes. A total of four buildings are studied considering different heights and different seismic codes. The OpenSees Program (the Open System for Earthquake Engineering Simulation) is used to perform nonlinear dynamic analyses of the structures. While spectral displacement (Sd), spectral acceleration (Sa) and peak ground acceleration (PGA) are chosen as intensity measures, maximum inter-story drift ratio (MIDR) and top displacement (Dtop) are selected as engineering demand parameters. For the dam age state definitions through threshold values on the EDPs, nonlinear static (pushover) analyses are conducted to pick the limit values of top displacements from the idealized pushover curves whereas limit values for MIDR are drawn from the Hazus MR4 Tech nical Document. For MSA, 11 stripes and 22 pairs of earthquake records for each stripe are used, while 44 sets of record pairs are used for cloud analysis. Fragility functions for the aforementioned buildings are developed by using two methods and compared to account for the epistemic uncertainty in the derivation of fragility functions.
Keywords: Earthquake risk analysis.; Earthquake resistant design -- Turkey -- Istanbul.